Human neutralizing antibodies against SARS-CoV-2 require intact Fc effector functions for optimal therapeutic protection - Winkler, Emma S.; Gilchuk, Pavlo; Yu, Jinsheng; Bailey, Adam L.; Chen, Rita E.; Chong, Zhenlu; Zost, Seth J.; Jang, Hyesun; Huang, Ying; Allen, James D.; Case, James Brett; Sutton, Rachel E.; et al. (Cell, 2021)
SARS-CoV-2 has caused the global COVID-19 pandemic. Although passively delivered neutralizing antibodies against SARS-CoV-2 show promise in clinical trials, their mechanism of action in vivo is incompletely understood. Here, we define correlates of protection of neutralizing human monoclonal antibodies (mAbs) in SARS-CoV-2-infected animals. Whereas Fc effector functions are dispensable when representative neutralizing mAbs are administered as prophylaxis, they are required for optimal protection as therapy. When given after infection, intact mAbs reduce SARS-CoV-2 burden and lung disease in mice and hamsters better than loss-of-function Fc variant mAbs. Fc engagement of neutralizing antibodies mitigates inflammation and improves respiratory mechanics, and transcriptional profiling suggests these phenotypes are associated with diminished innate immune signaling and preserved tissue repair. Immune cell depletions establish that neutralizing mAbs require monocytes and CD8+ T cells for optimal clinical and virological benefit. Thus, potently neutralizing mAbs utilize Fc effector functions during therapy to mitigate lung infection and disease. [Display omitted] •Neutralizing mAbs do not require Fc effector functions when given as prophylaxis•MAbs against SARS-CoV-2 require Fc effector functions for therapeutic protection•Fc engagement of mAbs decreases viral burden and mitigates lung inflammation•CD8+ T cells and monocytes are necessary for optimal Fc-dependent mAb protection Neutralizing human monoclonal antibodies (mAbs) against SARS-CoV-2 require Fc effector functions for optimal protection during post-exposure therapy, with intact mAbs reducing SARS-CoV-2 burden and lung disease in rodent models better than LALA-PG loss-of-function Fc variant mAbs and requiring monocytes and CD8+ T cells for optimal clinical and virological benefit.